An Application of Activity Based Costing Method as Alternative in Determination Hospital Appendictomic Prices the True Partner of Medan Year 2020 - Ali Napiah Nasution; Chrismis Novalinda Ginting; Frederick Frederick; Chandra Wilim (Budapest International Research and Critics University, 2022)
The main difference between the traditional system and the activity-based costing system lies in the number of cost drivers used, in determining the cost of goods, the activity-based costing system uses more cost drivers compared to the traditional cost system which only uses one cost driver. by unit. Activity-based costing (ABC) is estimated to be more efficient in determining hospital rates. The purpose of this study was to determine the application of the activity-based costing method as an alternative in determining appendectomy rates at Mitra Sejati Hospital Medan in 2020. This study was quantitative descriptive, the population of this study was all data and files in cases of patients with acute appendicitis at Mitra Sejati Hospital. Medan Year 2020. The results showed that the unit cost of an appendectomy at Mitra Sejati General Hospital Medan using the activity-based costing method was Rp. 21,763,871.7. There is a difference in the cost of appendectomy with the unit cost using the activity-based costing method and by using real cost calculations at Mitra Sejati General Hospital Medan in 2020 with a cost difference of Rp. 2,647.034.7 There is a difference in the cost of appendectomy with the unit cost using the activity-based costing method and by using real cost calculations at Mitra Sejati General Hospital Medan in 2020 with a cost difference of Rp. 2,647.034.7.